ANALYSIS OF SERVICE QUALITY IMPROVEMENT AND PRODUCT INNOVATION ON COMPETITIVE ADVANTAGE AND THEIR IMPACT ON INTEREST IN SAVING MILENIAL GENERATION IN MAKASSAR CITY - Djabir Hamzah; Maat Pono; Suciyana, Weni (Journal of Risk and Uncertainty Issues, 2023)
Analyzing the effect of service quality and product innovation on competitive advantage and their impact on the millennial generation's interest in saving in Makassar City is the objective of this study. The millennial generation is an important group in the economy and has shown different tendencies in financial behavior, especially in terms of saving. For this reason, financial institutions and banking service providers need to comprehend the factors that influence their propensity to save. This research employs a quantitative methodology to examine the millennial generation in Makassar City. According to the findings of this research, service quality has a favorable and considerable impact on competitive advantage. In this context, the higher the quality of services offered by financial institutions, the greater their competitive advantage. In addition, Product innovation has a positive and substantial effect on competitive advantage as well. Product innovation that is attractive and relevant to the needs of the millennial generation can enhance financial institutions' competitive advantage. In addition, the results of this study also show that competitive advantage has a positive and significant impact on the millennial generation's interest in saving in Makassar City. This research makes an important contribution to financial institutions and banking service providers in understanding the factors that influence the millennial generation's intention to save. In facing increasingly fierce competition, financial institutions can increase their competitive advantage by improving the quality of services provided and developing product innovations that are relevant to the needs of the millennial generation. Thus, they can increase the interest of the millennial generation in saving, which in turn will provide benefits for the growth and stability of the financial sector in Makassar City.